PTSD: Diagnosis, Evolution, and Treatment of Combat-Related Psychological/Psychiatric Injury - Corvalan, Juan C. (Mo Med, 2011)
The long Iraq and Afghanistan conflicts have thrust Combat Related Post-Traumatic Stress Disorder (CR-PTSD) into the public consciousness and promoted national dialogue on the incidence and results of war related psychological trauma. In the first of a two part series we outline our contemporary understanding of CR-PTSD, the evolution of the diagnosis throughout the history of modern warfare, its impact on the mind and body, and its treatment. PTSD has become the mental health issue of our time.